Nitrate uptake using mesoporous silica embedded with zero-valent palladium nanoparticles - Tong, C.; Eroglu, E.; Duan, X.; Lamb, R.; Jarrett, K.; Buckley, Craig; Raston, C. (Royal Society of Chemistry, 2015)
In situ reduction of palladium(II) acetylacetonate during the synthesis of SBA-15 mesoporous silica affords a material impregnated with palladium nanoparticles. The synthesis is at neutral pH and ambient conditions using a continuous flow vortex fluidic device with high shear dynamic thin films, followed by calcination. The SBA-15 is available with considerably reduced processing time relative to the conventional synthesis of mesoporous silica, with the material being effective for nitrate-nitrogen [NO3−-N] removal from aqueous solutions, at 41% within the first 16 hours, or around 36% for the same period after being recycled.